2021
DOI: 10.1007/s00148-021-00873-y
|View full text |Cite
|
Sign up to set email alerts
|

Child marriage and infant mortality: causal evidence from Ethiopia

Abstract: This study assesses the causal effect of child marriage on infant mortality. Using age discontinuities in exposure to a law that raised the legal age of marriage for women in Ethiopia, the study estimates that a 1-year delay in a woman’s age at cohabitation during her teenage years reduces the probability of her first-born child dying during infancy by 3.8 percentage points. This impact is closely linked to the effect of delaying cohabitation on women’s age at first birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Becker et al (1977) have laid out theoretical micro-foundations in their seminal work for why an early age at there is abundant advice against marrying younger in the popular press 3 focusing on young adulthood broadly, making the question policy relevant. While this advice is well-justified for teenage marriages for their far more critical negative consequences than divorce, such as adverse physical health, poverty, child mortality and crime (see Jensen & Thornton, 2003, Field & Ambrus, 2008, Garcia-Hombrados, 2017 for lowmiddle income countries, and see Hunt, 2006, Bharadwaj, 2015, and Dahl, 2010 for the USA), we show that it lacks empirical support for young adults beyond teen years.…”
Section: Introductionmentioning
confidence: 72%
“…Becker et al (1977) have laid out theoretical micro-foundations in their seminal work for why an early age at there is abundant advice against marrying younger in the popular press 3 focusing on young adulthood broadly, making the question policy relevant. While this advice is well-justified for teenage marriages for their far more critical negative consequences than divorce, such as adverse physical health, poverty, child mortality and crime (see Jensen & Thornton, 2003, Field & Ambrus, 2008, Garcia-Hombrados, 2017 for lowmiddle income countries, and see Hunt, 2006, Bharadwaj, 2015, and Dahl, 2010 for the USA), we show that it lacks empirical support for young adults beyond teen years.…”
Section: Introductionmentioning
confidence: 72%
“…As a result, there is abundant advice against marrying younger in the popular press 3 focusing on young adulthood broadly, making the question policy relevant. While this advice is well-justified for teenage marriages for their far more critical negative consequences than divorce, such as adverse physical health, poverty, child mortality and crime (see Jensen and Thornton 2003, Field and Ambrus 2008, Garcia-Hombrados 2017 for low-middle income countries, and see Hunt 2006, Bharadwaj 2015, and Dahl 2010 for the USA), we show that it lacks empirical support for young adults beyond teen years.…”
Section: Introductionmentioning
confidence: 73%
“…Additionally, age at first cohabitation with a spouse is negatively associated with pregnancy, motherhood and as well as adverse pregnancy outcomes. Literature has reported controversial findings regarding the association between marriage before 18 years and adverse maternal and child health outcomes such as pregnancy termination, unintended pregnancy, underutilization of maternal health services, female sterilization, stillbirth/miscarriage, infant mortality, child mortality, malnutrition [39][40][41][42][43]. Hospital-based studies have reported that teenage pregnancy itself is 'causally' associated with a poor obstetric outcomes such as perinatal death [44].…”
Section: Discussionmentioning
confidence: 99%